Total phenolic content, flavonoid concentration and antioxidant activity of indigenous herbs, physalis minima linn: article - Helling, Mealianny; Che Radzi, Nurhaslina; Mustapa, Ana Najwa; Che Yunus, Mohd Azizi (2019)
Physalis minima linn is a plant under the Solanaceae family having secondary metabolites with distinct biological activities. The total phenolic, total flavonoid and antioxidant activity on different parts (leaves, whole plant, stem, roots and fruits) of Physalis minima linn were analysed by the use of FolinCiocalteu method, aluminium chloride colorimetric method and 2,2’-diphenyl-1-picrylhydrazyl (DPPH) assay, respectively. Results demonstrated that leaves extract exhibited as the highest value of total phenolic content of 1125.42 ± 14.60 mg of gallic acid (GAE) equivalent per gram of plant (dry extract). The low value of IC50 indicated that leaves, whole plant and fruits can be deemed as a good candidates for natural plant sources of antioxidants with high value of antioxidant activity.